Pemberdayaan Masyarakat dalam Pencegahan dan Pengendalian Gangguan Kesehatan Mental Lansia di Kecamatan Slawi Kabupaten Tegal - Osie Listina; Musripah Musripah; Anisa Oktiawati; Reno Arkan Pratama; Rizad Pradivta (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Mental health disorders are increasingly recognized as a growing public health concern, particularly among the elderly population. National health survey data (Riskesdas) indicate a significant rise in the prevalence of mental disorders in Indonesia. In Slawi Sub-district, Tegal Regency, the burden is considerable, with 117 active patients and 3,602 severe cases of mental illness recorded at the regency level. This community engagement program was designed to empower elderly groups, particularly members of posyandu lansia within the Prolanis program, through education, counseling, and multidisciplinary collaboration involving psychology, pharmacy, and nursing. The intervention was implemented through socialization, training, development of educational booklets, mentoring, and evaluation using pre-test and post-test assessments. Findings demonstrated improved knowledge and more positive attitudes toward mental health among elderly participants. This program contributes to the achievement of the Sustainable Development Goals (SDGs), specifically Goal 3 (Good Health and Well-being), and aligns with the 2024 Work Plan of the Tegal Regency Health Office. Moreover, it highlights the potential of community-based empowerment interventions as a model to enhance elderly quality of life and reduce stigma toward people with mental disorders.